Host Resistance to Bacterial Infection Varies Over Time, but Is Not Affected by a Previous Exposure to the Same Pathogen - Acuña Hidalgo, Beatriz; Armitage, Sophie A. O. (Frontiers in Physiology, 2022)
Immune priming describes the phenomenon whereby after a primary pathogen exposure, a host more effectively fights a lethal secondary exposure (challenge) to the same pathogen. Conflicting evidence exists for immune priming in invertebrates, potentially due to heterogeneity across studies in the pathogen species tested, the antigen preparation for the primary exposure, and the phenotypic trait used to test for priming. To explore these factors, we injected Drosophila melanogaster with one of two bacterial species, Lactococcus lactis or Providencia burhodogranariea, which had either been heat-killed or inactivated with formaldehyde, or we injected a 1:1 mixture of the two inactivation methods. Survival and resistance (the inverse of bacterial load) were assessed after a live bacterial challenge. In contrast to our predictions, none of the primary exposure treatments provided a survival benefit after challenge compared to the controls. Resistance in the acute phase, i.e., one day post challenge, separated into a lower- and higher-load group, however, neither group varied according to the primary exposure. In the chronic phase, i.e., seven days post challenge, resistance did not separate into two groups, and it was also unaffected by the primary exposure. Our multi-angled study supports a view of immune priming that requires specific circumstances to occur, rather than it being a ubiquitous aspect of insect immunity.